2018
DOI: 10.3390/molecules23071640
|View full text |Cite
|
Sign up to set email alerts
|

Development of Dermal Films Containing Miconazole Nitrate

Abstract: This study aims to develop new antifungal dermal films based on their mechanical properties (elongation, adhesion, behaviour towards vapour moisture) and the in vitro availability of miconazole nitrate, used as a pharmaceutical active ingredient in various concentrations. The three polymeric films prepared were translucent or shiny, with the surface of 63.585 cm2, 0.20–0.30 mm thickness, and content of miconazole nitrate of 3.931 or 15.726 mg·cm2. The mechanical resistance and elongation tests demonstrated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…It was observed that SI was ALG concentration-dependent -formulation P3 with high ALG concentration possessed higher SI properties. Similarly, Sarheed et al noted that swelling ability was increased with the Folding endurance was measured to determine the rupturing resistance of designed buccal films, and, in all formulations, it was over 100 times, exhibiting good flexibility [18].…”
Section: Swelling Studymentioning
confidence: 97%
See 1 more Smart Citation
“…It was observed that SI was ALG concentration-dependent -formulation P3 with high ALG concentration possessed higher SI properties. Similarly, Sarheed et al noted that swelling ability was increased with the Folding endurance was measured to determine the rupturing resistance of designed buccal films, and, in all formulations, it was over 100 times, exhibiting good flexibility [18].…”
Section: Swelling Studymentioning
confidence: 97%
“…In addition, it was observed that placebo formulations (P1-P4) were characterized by higher TS, E%, and E values than POS-loaded formulations (F1-F4), proving that the addition of the drug substance weakens mechanical properties. Folding endurance was measured to determine the rupturing resistance of designed buccal films, and, in all formulations, it was over 100 times, exhibiting good flexibility [18].…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…The increasing number of stress conditions caused by the diversification of activities conducted in modern society, associated with the occurrence of the corresponding pollution factors and the diversity of microbial agents, in particular caused by the increased mobility of people all over the world, led, in addition to the appearance of new diseases, to the occurrence and the diversification of fungal infections. The development of pharmaceutical forms with miconazole nitrate (MN) for external use can bring various benefits to patients presenting resistance to classic antifungal forms because of the fact that the active drug lasts longer in the tissue, acting as a slow release product [7,8]. Repeated administration leads to an accumulating effect of multiple doses in the stratum corneum, which causes the disappearance of fungal infection [6,28].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, in situ film-forming systems (on the skin, after spreading in a thin layer) -FFSs which form a film on the skin after spreading in a thin layer, have been developed as a new approach to be used as an alternative to both conventional and transdermal topical formulations [12]. In this paper, four pharmaceutical substances were selected as potential active ingredients ( Figure 1) that could be useful in the form of film-forming systems with dermal and/or transdermal delivery: adapalene (ADA) [23,84], levofloxacin (LEV) [36,69], meloxicam (MEL) [16], and miconazole nitrate (MIC) [10]. These therapeutic agents have some significant physicochemical properties (Table I) based on which they can be individually used to treat various skin diseases: skin candidiasis, acne vulgaris, other skin infections, etc.…”
Section: Introductionmentioning
confidence: 99%